2004
DOI: 10.1002/pen.20042
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the evolution of PET branching through chemorheology

Abstract: There is a high interest in modifying the rheological properties of polyethylene terephthalate (PET) through structural modifications while maintaining its thermoplastic nature. This article reports real‐time spectroscopic and rheological monitoring of the effects of reactive melt modification of PET with a multi‐functional epoxide—triglycidyl isocyanurate (TGIC)—that lead to chain extension/branching and subsequently formation of gel‐like structures. An infrared spectroscopic technique to monitor the simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…19,20 Xia et al 21 investigated the batch foaming behavior of PMDA-modified PET, a broad foaming temperature window was obtained for PET modified with 0.8 wt % PMDA. The improvement of viscoelasticity caused by some epoxy-based modifiers, such as tetraglycidyl diamino diphenyl methane 22,23 and triglycidyl isocyanurater [24][25][26] had also been demonstrated. Joncryl is a multi-functional epoxy oligomer and can be used to increase the melt properties of poly(lactic acid).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Xia et al 21 investigated the batch foaming behavior of PMDA-modified PET, a broad foaming temperature window was obtained for PET modified with 0.8 wt % PMDA. The improvement of viscoelasticity caused by some epoxy-based modifiers, such as tetraglycidyl diamino diphenyl methane 22,23 and triglycidyl isocyanurater [24][25][26] had also been demonstrated. Joncryl is a multi-functional epoxy oligomer and can be used to increase the melt properties of poly(lactic acid).…”
Section: Introductionmentioning
confidence: 99%
“…For polyesters, chain-extension consists in increasing the molecular weight by bridging the hydroxyl or carboxyl reactive-end groups using bi or poly-functional molecules. For PET, branching was obtained by reaction with pyromellitic dianhydride, [24][25][26], and with various epoxy-based chain-extenders, [27][28][29][30][31]. For PLA, various diisocyanate were investigated for this purpose [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…As PMDA was not that effective for modification of r‐PET, two multifunctional epoxides, i.e., TGIC and ADR, as the chain extenders were used to investigate their modification effects on the r‐PET. Different from PMDA reacting only with one terminal hydroxyl group of PET, the epoxides can react with both the carboxyl and hydroxyl groups of PET by esterification and etherification, and the secondary hydroxyls formed from these reactions may further react with carboxyl or epoxy groups leading to branching or cross‐linking . At the extrusion conditions of main motor's rotation speed of 240 rpm, the IV of the reactive extruded r‐PET with the addition of different concentrations of TGIC or ADR is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…showed that the IV of recycled bottle‐grade PET effectively increased from 0.69 to 0.85 dL/g with bis‐oxazolines as the chain extender. Other chain extenders such as pentaerythritol (PENTA) and triglycidyl isocyanurate (TGIC) were also used to improve the IV of PET. Adding different chain extenders together could also effectively achieve the chain extension.…”
Section: Introductionmentioning
confidence: 99%